The Influence of Awareness Level, Financial Education, and Platform Availability on the Investment Interest of Master’s Students in Management Science at Universitas Pendidikan Ganesha in Cryptocurrency - Rika Persada Jati; Putu Indah Rahmawati; Fridayana Yudiaatmaja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In Indonesia, cryptocurrency has gained strong interest, especially among young people, supported by high internet penetration and rising digital literacy. Although adoption continues to grow with millions of users and the presence of major platforms, challenges such as strict regulations and low financial literacy remain, while social media also plays a role in increasing investment interest. This study aims to analyze the influence of awareness level, financial education, and platform availability on the investment interest of master’s students in management science at universitas pendidikan ganesha in cryptocurrency. The population in this study consists of Master’s students enrolled at Universitas Pendidikan Ganesha. Students in this category are expected to have sufficient knowledge about cryptocurrency and to provide relevant information regarding their interest in investment. The data analysis techniques used in this study include descriptive analysis and inferential analysis. The results show that Awareness Level (X1), Financial Education (X2), and Platform Availability (X3) have a significant effect on the investment interest of Master’s students in Management Science at Ganesha University of Education in cryptocurrency, as indicated by significance values below 0.05.